2017
DOI: 10.1038/s41598-017-14839-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the CRISPR-Cas system in bacteriophages active on epidemic strains of Vibrio cholerae in Bangladesh

Abstract: CRISPR-Cas (clustered regularly interspersed short palindromic repeats-CRISPR-associated proteins) are microbial nuclease systems involved in defense against phages. Bacteria also resist phages by hosting phage-inducible chromosomal islands (PICI) which prevent phage reproduction. Vibrio cholerae which causes cholera epidemics, interacts with numerous phages in the environment and in cholera patients. Although CRISPR-Cas systems are usually carried by bacteria and archea, recently V. cholerae specific ICP1 pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 42 publications
5
41
0
Order By: Relevance
“…To evaluate if the fixation of CRISPR in ICP1 is necessitated by co-circulating PLE in epidemic V. cholerae , we determined the prevalence of PLE over the same near two-decade long period in Dhaka. Combined with previous analyses (12,21), we observed an increase in the prevalence of PLE(+) V. cholerae in epidemic sampling over time (Fig. 1c).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…To evaluate if the fixation of CRISPR in ICP1 is necessitated by co-circulating PLE in epidemic V. cholerae , we determined the prevalence of PLE over the same near two-decade long period in Dhaka. Combined with previous analyses (12,21), we observed an increase in the prevalence of PLE(+) V. cholerae in epidemic sampling over time (Fig. 1c).…”
Section: Resultssupporting
confidence: 86%
“…We set out to compare ICP1 and PLE from contemporary cholera patient stool samples to previously identified isolates from the International Centre for Diarrhoeal Disease Research, Bangladesh (ICDDR,B) in Dhaka, Bangladesh (13,21). We isolated eight new ICP1 isolates from cholera patient stool samples collected between 2015-2017 and found that all isolates harbor CRISPR-Cas.…”
Section: Resultsmentioning
confidence: 99%
“…These ranged from occurrences in 18 genomes (n=12) to singletons (n=14) (Figure 3) with several patterns of accessory ORF co-occurrence (Table S2). The most obvious example was the CRISPR-Cas locus which was previously known to reside in 8 of these genomes [13,15] and confirmed through our annotation methods. Other examples of sequential ORF co-occurrence included a locus containing ORFs 115, 116, 117, 117.1 and 118 which were found in the same five genomes, ORFs 160, 162, 163 in a different set of five overlapping genomes and ORFs 222, 223, 225 in 15 genomes.…”
Section: Resultssupporting
confidence: 69%
“…Previous work has identified a V. cholera O1-specific [10] lytic myoviridae bacteriophage (ICP1) to be of particular interest in this system [11]. In Bangladesh, ICP1 has been found in water samples [12,13] and it has been identified as the dominant phage in cholera patient stool samples since 2001 [11]. The persistence of this phage over time indicates that V. cholerae has strategies to limit ICP1 predation, and that ICP1 can evolve to overcome such defenses.…”
Section: Introductionmentioning
confidence: 99%
“…Because of ICP3’s fickle nature in water, it is possible that maintenance of ICP3 in Bangladesh relies primarily upon rapid transmission between people such as occurs within households (32). Of 29 sequences reported for environmental V. cholerae phages (11, 25, 29, 33), 41% corresponded to ICP3-like phages. This result is striking, since our model does not support the notion that ICP3 can replicate in nutrient-limiting aquatic environments.…”
Section: Discussionmentioning
confidence: 99%